Analisis Kuat Tekan Beton Geopolimer Dengan Bahan Tambah Serat Plastik HDPE - Mayumi, Emilia; Setiawan, Arman; Yuniarto, Eka (Program Studi Teknik Sipil Universitas Bosowa, 2025)
In today's infrastructure development, concrete is one of the most widely used structural materials in a construction as its basic material. To produce cement, factories produce waste gases and waste particles that can pollute the air. In this research, geopolymer concrete binder is a breakthrough to replace Portland cement binder. In this study, the added material used is HDPE plastic fiber. This research is an experiment conducted at the laboratory of concrete structures and materials at the University of Bosowa Makassar. The composition of the geopolymer concrete mixture obtained was fly ash (2.47kg), NaOH (0.56kg), Na2SiO3 (0.83kg), water (1.24kg), sand (3.60kg), crushed stone 0.5-1 (5.14kg). The HDPE plastic fibers used in this study were 5%, 10%, 15% and 20% by weight of fly ash. From the results of research using HDPE plastic fiber composition of 5%, 10% 15%, 20% respectively, the results obtained are 18,401 Mpa, 15,664 Mpa, 13,022 Mpa, 11,323 Mpa.